DAMPAK GRADASI AGREGAT DENGAN DUA VARIASI ASPAL TERHADAP SIFAT CAMPURAN BETON ASPAL - Mulyono Mulyono; Edy Pramono; Eva Azhra Latifa (Jurnal Poli-Teknologi, 2011)
Abstract This research meant to observe impact of aggregate gradation with two kind of asphalt towards asphaltic concrete properties. Asphalt Cement Wearing Course research which is applied to aggregate gradation above and below Restriction zone according to Bina Marga December 2005 specification. Both of asphalt has same viscosity but come from different resources suggest different behavior at temperature impact. Laboratory test do to determine void in mineral aggregate, void in mixture and void filled with asphalt, stability and flow occurred. The conclusions are: (1) For two kind of asphalt Pertamina and Shell, aggregate gradation above restriction zone better than below, however some result does not show any patron. (2) Two kind of asphalt with same penetration have same asphalt optimum percentages, 6 - 6,5%. (3) Aggregate gradation above restriction zone has 1312 kg -812 kg stability with 3,97% - 3,93% void in mixture with 10% filler. (4) Refusal test for two kind of asphalt’s result shows that smallest void in mixture and biggest void filled with asphalt occur at above restriction zone. Keywords: aggregate gradation, restricition zone, void, stability, flow.